PTPN22 1858C>T Polymorphism Distribution in Europe and Association with Rheumatoid Arthritis: Case-Control Study and Meta-Analysis - Totaro, Michele Ciro; Tolusso, Barbara; Napolioni, Valerio; Faustini, Francesca; Canestri, Silvia; Mannocci, Alice; Gremese, Elisa; Bosello, Silvia Laura; Alivernini, Stefano; Ferraccioli, Gianfranco (PloS one, 2011)
The PTPN22 rs2476601 polymorphism is associated with rheumatoid arthritis (RA); nonetheless, the association is weaker or absent in some southern European populations. The aim of the study was to evaluate the association between the PTPN22 rs2476601 polymorphism and RA in Italian subjects and to compare our results with those of other European countries, carrying out a meta-analysis of European data. A total of 396 RA cases and 477 controls, all of Italic ancestry, were genotyped for PTPN22 rs2476601 polymorphism. Patients were tested for autoantibodies positivity. The meta-analysis was performed on 23 selected studies. The PTPN22 T1858 allele was significantly more frequent in RA patients compared to controls (5.7% vs. 3.7%, p = 0.045). No clear relationship arose with the autoantibodies tested. The 1858T allele frequency in Italian RA patients was lower than the one described in northern European populations and similar to the frequency found in Spain, Turkey, Greece, Tunisia. A clear-cut North-South gradient arose from the analysis. The PTPN22 T1858 allele is associated with RA in the Italian population. A North-South gradient of the allele frequency seems to exist in Europe, with a lower prevalence of the mutation in the Mediterranean area.